Chromosomal periodicity and positional networks of genes in Escherichia coli - Anthony Mathelier; Alessandra Carbone (Molecular Systems Biology)
Abstract The structure of dynamic folds in microbial chromosomes is largely unknown. Here, we find that genes with a highly biased codon composition and characterizing a functional core in Escherichia coli K12 show to be periodically distributed along the arcs, suggesting an encoded three‐dimensional genomic organization helping functional activities among which are translation and, possibly, transcription. This extends to functional classes of genes that are shown to systematically organize into two independent positional gene networks, one driven by metabolic genes and the other by genes involved in cellular processing and signaling. We conclude that functional reasons justify periodic gene organization. This finding generates new questions on evolutionary pressures imposed on the chromosome. Our methodological approach is based on single genome analysis. Given either core genes or genes organized in functional classes, we analyze the detailed distribution of distances between pairs of genes through a parameterized model based on signal processing and find that these groups of genes tend to be separated by a regular integral distance. The methodology can be applied to any set of genes and can be taken as a footprint for large‐scale bacterial and archaeal analysis.